What about her? Oil palm cultivation and intra-household gender roles. (July 2022) - Mehraban, Nadjia; Debela, Bethelhem Legesse; Kalsum, Ummi; Qaim, Matin
Highlights: Associations between oil palm cultivation and gender roles analyzed with survey data from Indonesian farm households. In comparison to more traditional crops, oil palm is labor-saving, especially for women. Women's time saved is reallocated to household chores, care work, and leisure, not off-farm employment. Lower involvement of women in income-earning activities is economically disempowering. Abstract: Oil palm is one of the fastest expanding crops in tropical regions, leading to massive land-use changes and far-reaching social implications. In Indonesia, much of the oil palm land is cultivated by smallholder farmers. While household income effects of oil palm cultivation were analyzed in previous studies, effects on intra-household gender roles are not yet well understood. Here, we use sex-disaggregated survey data from farm households in Sumatra to examine how oil palm cultivation – in comparison to cultivating traditional crops – is associated with women's and men's time allocation and decision-making power. Women in oil palm cultivating households spend much less time in farming and more time for household chores and leisure than women in households only cultivating traditional crops. These differences increase with the share of the farm area under oil palm, as oil palm requires less labor than traditional crops. While a reduction in women's workload can have positive social effects, lower involvement in farming can also be associated with a loss in female autonomy. Indeed, our data suggest that oil palm cultivation is associated with women having less decision-making power in terms of farm management and income control. These insights can help to design policies for more gender-equitable rural development.